1975
DOI: 10.1002/macp.1975.021760703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmakologisch aktive polymere, 8.Poly[2‐(methylsulfinyl)äthylacrylat]e und ihre vermittelnde wirkung auf die transkutane resorption von pharmaka

Abstract: ZUSAMMENFASSUNG:Poly [2-(methylsulfinyl)athylacrylat] (2a) und Poly[2-(methylsulfinyl)athylmethacrylat] (2b) wurden synthetisiert und auf ihre vermittelnde Wirkung bei transkutaner Resorption einiger Pharmaka untersucht. 2b verbesserte die Resorption der Phosphorsaureester Dimethoat@ und Paraoxon@ und der p-Aminohippursaure und war etwa mit der Wirksamkeit von DMSO vergleichbar.Ein geringer penetrationsfordernder Effekt ergab sich fur Dinitrochlorbenzol. Nicht beeinflurjt wurde die dermale Resorption von Isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Polymers based on sulfoxides are known for their very low cytotoxicity [29,30,31], and the idea to use them in a biological environment is not new. In the mid 1970s, Helmut Ringsdorf already saw the potential advantages of sulfoxide-containing polymers and studied side-chain sulfoxide polyacrylates (in particular poly(2-(methylsulfinyl)ethyl acrylate), PMSEA) as biocompatible and bioresorbable penetration enhancers [32]. PMSEA was recently proposed again by Matyjaszewski with more modern syntheses based on Atom Transfer Radical Polymerization (ATRP) [29], electrochemically mediated ATRP (eATRP) [33], and surface-initiated ATRP [34].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers based on sulfoxides are known for their very low cytotoxicity [29,30,31], and the idea to use them in a biological environment is not new. In the mid 1970s, Helmut Ringsdorf already saw the potential advantages of sulfoxide-containing polymers and studied side-chain sulfoxide polyacrylates (in particular poly(2-(methylsulfinyl)ethyl acrylate), PMSEA) as biocompatible and bioresorbable penetration enhancers [32]. PMSEA was recently proposed again by Matyjaszewski with more modern syntheses based on Atom Transfer Radical Polymerization (ATRP) [29], electrochemically mediated ATRP (eATRP) [33], and surface-initiated ATRP [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to regular ethers, the nature of sulfur provides the possibility to functionalize thioethers via oxidation, alkylation, and alkoxylation, which can lead to interesting material properties. In the 1970s, Ringsdorf and co-workers demonstrated that oxidized poly­[2-(methylsulfinyl)­ethyl acrylate] and poly­[2-(methylsulfinyl) methacrylate] can serve as polymeric resorption enhancing alternatives to low molecular weight DMSO. , Thirty years later, Hubbell, Tirelli, and co-workers recognized the potential of polythioethers as redox-responsive nanocarriers for inflammation targeting . In the oxidative milieu of inflamed tissue, hydrophobic thioethers are oxidized to more polar sulfoxides or sulfones, leading to a change in the hydrophobic/hydrophilic balance with disassembly of the nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the oxidized products is also important: sulfoxide‐containing polymers were initially studied by the group of Ringsdorf in the 1970s with very promising results in terms of extremely low in vivo toxicity 41, 42. On the other hand, low‐molecular‐weight depolymerization products and/or sulfone‐containing substrates may be considerably more toxic.…”
Section: Introductionmentioning
confidence: 99%